Impacts of Coil Treatment on Anxiety and Depression in Emphysema - Tugce Toker Ugurlu; Erhan Ugurlu (Canadian Respiratory Journal)
Chronic obstructive pulmonary disease (COPD) is a widespread, preventable, and treatable disease. Emphysema is one of the primary components of COPD and manifests itself via decrease in elastic recoil, hyperinflation, and increase in air trapping. Various lung-volume-reduction treatments have come up in recent years for late-stage emphysema patients. Mental disorders and especially anxiety and depression are among the frequently encountered comorbid cases observed in COPD. The aim of our study was to examine the impact of coil treatment applied for late-stage COPD-emphysema diagnosed patients on the accompanying anxiety and depressive symptoms. A total of 21 patients diagnosed with emphysema that meet the suitability criteria for coil treatment were included in the study. The accompanying anxiety and depressive symptoms of the patients were assessed via beck anxiety inventory (BAI) and beck depression inventories (BDI-I) prior to the procedure and one month later. All patients were male with an age average of 66.5 ± 5.5 (57–76). Among patients without a psychiatric diagnosis, BAI scores before and after coil treatment were determined, respectively, as 12.1 ± 6.3 (4–26) and 11.2 ± 9.3 (0–28), whereas BDI-I scores before and after coil treatment were determined, respectively, as 13.5 ± 10.4 (1–31) and 8.8 ± 10.6 (0–34), with a statistically significant difference between them. Also among patients with a psychiatric diagnosis, both anxiety and depressive symptoms decreased after coil treatment, and this reduction was found more significant for anxiety. Coil treatment as a current and novel treatment method for COPD-emphysema diagnosed patients with or without psychiatric comorbidity has a positive impact on anxiety and depressive symptoms.